Mary Roussou- Sinclair, Victorian travellers in Cyprus: A garden of their own, Cyprus Research Centre Texts and Studies of the History of Cyprus - XLIV, Nicosia 2002. - Πολυκανδριώτη Ουρανία (Σύγκριση/Comparaison/Comparison, 2017)
Δεν διατίθεται περίληψη.